Pandemic! And now? Banned bodies: Virtual museum of sustainable experiences - Magalhães, Consuelo Salvaterra; Alves, Luanda dos Santos; de Faria, Sandra Elizabete Carlos Ribeiro (Seven Editora, 2023)
This work aims to highlight the importance of using social media in the transmission of scientific knowledge in the context of social isolation/distance. Based on the premise of inseparability between teaching, research, and extension in universities, it is understood here that extension activities and the sharing of scientific knowledge must be reinvented and made possible through social media – WhatsApp, YouTube, Instagram, and Blog, among others. The current pandemic context of Covid-19 initially stalled individuals who are in constant search for new forms of readaptation in face of this reality. Sustainable experiences via virtual museum is another way in which the extension project “Creativity with Sustainability: exchanging experiences in a virtual format” aspires to spread environmental education with demonstrations of its actions with the reuse of solid waste. DOI: https://doi.org/10.56238/devopinterscie-089